2006
DOI: 10.1073/pnas.0510877103
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of replicative senescence in hepatocellular carcinoma-derived cells

Abstract: immortality ͉ liver cancer ͉ SIP1 ͉ telomerase ͉ p53

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 33 publications
5
60
0
Order By: Relevance
“…Inducible expression systems were used in most of the previous studies involving ZEB-2 overexpression (Comijn et al, 2001;Vandewalle et al, 2005), which is difficult to adapt for MCF10A cells. ZEB-2 has recently been shown to induce replicative senescence in certain cell types, suggesting that the activity of ZEB-2 is dependent on gene dose as well as cellular context (Ozturk et al, 2006). We observed the loss or reduced expression of p63 in both p65 and ZEB-1 overexpressing cells.…”
Section: Discussionsupporting
confidence: 48%
“…Inducible expression systems were used in most of the previous studies involving ZEB-2 overexpression (Comijn et al, 2001;Vandewalle et al, 2005), which is difficult to adapt for MCF10A cells. ZEB-2 has recently been shown to induce replicative senescence in certain cell types, suggesting that the activity of ZEB-2 is dependent on gene dose as well as cellular context (Ozturk et al, 2006). We observed the loss or reduced expression of p63 in both p65 and ZEB-1 overexpressing cells.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, SIP1 was shown to directly repress cyclin D1 (Mejlvang et al, 2007). Also, induced expression of SIP1 was reported to be partly responsible for hTERT repression in hepatocellular carcinoma cells (Ozturk et al, 2006). On the other hand, SIP1 may be implicated in tumor development irrespective of its role in inducing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…hTERT repression in breast cancer cells was partly mediated by SIP1 in a TGF-β dependent manner (Lin and Elledge, 2003). Also, analysis of senescence arrest of clonal hepatocellular carcinoma cells revealed SIP1 as a mediator of hTERT repression (Ozturk et al, 2006). Impaired G1/S progression was observed upon repression of cyclin D1 by SIP1 (Mejlvang et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Here we demonstrated that SIP1 significantly repressed G 1 /S transition in RT112 cells, whereas the effect of ZEB1 was insignificant. In hepatocellular carcinoma cells, SIP1 repressed hTERT, resulting in replicative senescence (24). In contrast, ZEB1 was required for proliferation of mouse embryo fibroblasts, and ZEB1 Ϫ/Ϫ mouse embryo fibroblasts underwent premature replicative senescence (25).…”
Section: Discussionmentioning
confidence: 99%